The Role of Islamic Education on Interfaith Tolerance - Achmad Risqi Fanani; Aan Sanusi (IRDH International Journal of Social Sciences & Humanities, 2024)
Islamic religious education (PAI) becomes a subject that is able to provide insight to students, in social life in their respective environments. In this case, PAI education should be able and play an important role in teaching inter-religious tolerance to students. The research method used is qualitative research with a literature study. Mutual respect in faith and belief is a very comprehensive Islamic concept. We should act to protect and help each other without questioning differences in belief. The most deeply rooted principle in Islamic thought that supports a theology of tolerance is the belief in a natural religion, which is embedded in all human beings, and human goodness is a natural consequence of this principle.